High-Quality Genome Assembly of Olea europaea subsp. cuspidata Provides Insights Into Its Resistance to Fungal Diseases in the Summer Rain Belt in East Asia - Wang, Li; Zhang, Jianguo; Peng, Dan; Tian, Yang; Zhao, Dandan; Ni, Wanning; Long, Jinhua; Li, Jinhua; Zeng, Yanfei; Wu, Zhiqiang; Tang, Yiyun; Wang, Zhaoshan (Frontiers in Plant Science, 2022)
The olive tree (Olea europaea L.) is the most iconic fruit crop of the Mediterranean Basin. Since introduced into China in the 1960s, the summer rain climate makes it susceptible to pathogens, leading to some olive diseases. Olea europaea L. subsp. cuspidata is natively distributed in Yunnan province of China. It has smaller fruit, lower oil content, and higher resistance compared to subsp. europaea, which makes subsp. cuspidata a critical germplasm resource to be investigated. Here, a high-quality genome of subsp. cuspidata with 1.38 Gb in size was assembled and anchored onto 23 pseudochromosomes with the mounting rate of 85.57%. It represents 96.6% completeness (BUSCO) with a contig N50 of 14.72 Mb and a scaffold N50 of 52.68 Mb, which shows a significant improvement compared with other olive genomes assembled. Evaluation of the genome assembly showed that 92.31% of resequencing reads and an average of 96.52% of assembled transcripts, could be aligned to the assembled genome. We found that 66 positive selection genes were belonging to the term of response to stimulus based on GO analysis, among which, evm.model.Chr16.1133 was shared with the results of transcriptome analysis. This gene belongs to the susceptible gene and negatively regulates the disease resistance process. Furthermore, we identified the Cercospora genus which causes the leaf spot disease in the infected leaves. The high-quality chromosome-level genomic information presented here may facilitate the conservation and utilization of germplasm resources of this subspecies and provide essential genetic basis for further researches into the differences in oil content and resistance between subsp. cuspidata and europaea.